An 87-year sedimentary record of mercury contamination in the Old Yellow River Estuary of China. (October 2018) - Ge, Meng; Liu, Guijian; Liu, Yuan; Yuan, Zijiao; Liu, Houqi
Abstract: A sediment core, spanning from the year 1925 ± 3.03 to 2012, was collected for analyzing historical distribution of mercury (Hg) in the Old Yellow River Estuary (OYRE), China. The Hg concentrations in the sediment core ranged from 14 to 351 ng g −1, with the high values occurred in the middle layers (1960–1996), which may be resulted from intensive human activities during this period, such as oil exploitation and booming of petrochemical industry, salt chemical industry and chlor-alkali plants. A significant positive correlation was found between THg and loss on ignition (LOI). The main fraction of Hg existed in residual part while the fraction that was easy to leach out from sediments accounted for only a small portion according to the results of BCR sequential extraction procedure. Multiple ecological risks indices and guidelines of Hg indicated that the sedimentary record presented an "intermediate state" for Hg contamination in the OYRE. Highlights: High mercury (Hg) concentrations in studied core sediments were consistent with intensive human activities. A significant positive correlation was found between THg and loss on ignition (LOI). The major part of Hg in sediments was not bioavailable. The sediments of the Old Yellow River Estuary presented an "intermediate state" for ecological risks of Hg contamination.